EKSISTENSI “PASAR SEMAWIS” SEBAGAI SALAH SATU STRATEGI REVITALISASI KAWASAN PECINAN SEMARANG - Edi Purwanto (TEKNIK, 2010)
Revitalization is one of preservation kinds with adapting old building that is impractical to serve new use and inthe same time, to prevent the original characteristics. Revitalization can be done without or with changingbuilding formation. Sometimes, it really cannot be avoided if it is viewed from benefit expense analysis, it doesnot bring benefit to be preserved, so that, let the building façade be prevented, thus, the observer can imaginecity face in the past time.Revitalization effort of old city is not merely effort to preserve building, but also effort that has broughteconomic life in the less developed area. Preservation effort at the moment is holistic effort that aims to givebetter society life quality based on old resource power and to do life injection that is interesting and creative andsustainable, with involving society by calculating economy value. Management is instrument to achieve aimincluding society total involvement that is people centered management-oriented.Revitalization of Chinatown of Semarang area shall be read as an effort to bring back Chinatown area that hasethnic specification. Revitalization effort also has aim to bring Chinatown area life as well as to be tourismdestination as it has been implemented in several other countries, like Singapore, Australia, Malaysia andseveral others.One effort to fulfill revitalization of Chinatown area of Semarang is to give activity stimuli that is hoped to beable to be tourist’s interest. That interest is “Pasar Semawis”that is night fair in Chinatown area of Semarang.“Pasar Semawis” is only a part of revitalization. In the other word, if the revitalization is the aim, thus, “PasarSemawis” is one instrumen used to fulfill it.